Respostas
respondido por:
1
Oi :) Eis o passo a passo:
![y= \frac{1}{ \sqrt{x} } \\ \\ y= \frac{1}{ x^{ \frac{1}{2} } } \\ \\ y=x^{ -\frac{1}{2} } \\ \\ y'=- \frac{1}{2} x^{ -\frac{1}{2} -1} \\ \\ y'=- \frac{1}{2} x^{ -\frac{3}{2}} \\ \\ y'=- \frac{1}{2 x^{ \frac{3}{2}}} \\ \\ y'=- \frac{1}{2 \sqrt{x^3}} y= \frac{1}{ \sqrt{x} } \\ \\ y= \frac{1}{ x^{ \frac{1}{2} } } \\ \\ y=x^{ -\frac{1}{2} } \\ \\ y'=- \frac{1}{2} x^{ -\frac{1}{2} -1} \\ \\ y'=- \frac{1}{2} x^{ -\frac{3}{2}} \\ \\ y'=- \frac{1}{2 x^{ \frac{3}{2}}} \\ \\ y'=- \frac{1}{2 \sqrt{x^3}}](https://tex.z-dn.net/?f=y%3D+%5Cfrac%7B1%7D%7B+%5Csqrt%7Bx%7D+%7D++%5C%5C+%5C%5C++y%3D+%5Cfrac%7B1%7D%7B+x%5E%7B+%5Cfrac%7B1%7D%7B2%7D+%7D+%7D++%5C%5C++%5C%5C+y%3Dx%5E%7B+-%5Cfrac%7B1%7D%7B2%7D+%7D+%5C%5C++%5C%5C+y%27%3D-+%5Cfrac%7B1%7D%7B2%7D+x%5E%7B+-%5Cfrac%7B1%7D%7B2%7D+-1%7D+%5C%5C++%5C%5C+y%27%3D-+%5Cfrac%7B1%7D%7B2%7D+x%5E%7B+-%5Cfrac%7B3%7D%7B2%7D%7D++%5C%5C++%5C%5C+y%27%3D-+%5Cfrac%7B1%7D%7B2+x%5E%7B+%5Cfrac%7B3%7D%7B2%7D%7D%7D+++%5C%5C++%5C%5C++y%27%3D-+%5Cfrac%7B1%7D%7B2++%5Csqrt%7Bx%5E3%7D%7D)
evelyn241294:
vlw :)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás